Mobile robot : Transmitter module - Ng, Kok Ming (2007)
In this technology era, robots have become a common device to help human to do several of work especially those dangerous or heavy work that not easily done by human kind. Thus, there must be a communication between the robots and the human. The robots would be able to communicate with the operator through computer. This project is concern on the FM wireless communication between the computers with the robot. It requires to construct a mobile robot from scratch and a parallel port interface board enabling computer communication via the parallel port. The robot can measure the light density and the temperature within it and it also can perform obstacle detection and avoidance. Half-duplex communication is performed to suit the transmitter and receiver modules of the same carrier frequency. Acknowledged and unacknowledged protocol communication is implementted to demonstrate the efficiency in bi-directional PC-Robot communication. As a result, this robot can be implemented as the device to scout the parameter of a hazard area.